Analisis Beban Kerja Mental Pada Stasiun Boiler Dan Pengepresan Crude Palm Oil (Cpo) Dengan Menggunakan Metode Nasa TLX PT. Anugrah Fajar Rezeki - Tavren, Aidil Rizky Nugraha; Zeki, Muhammad (Program Studi Teknik Industri, Fakultas Teknik. Universitas Samudra, 2023)
This study analyzed mental workload at the Boiler and Crude Palm Oil (CPO) Pressing Station at PT. Anugrah Fajar Rezeki using the NASA-TLX method. Mental workload is important to measure because it affects the performance, safety, and health of workers. Data were collected by distributing questionnaires to operators on duty at both stations. NASA-TLX measures six dimensions of workload, namely mental load, physical load, temporal load, performance, effort, and frustration levels. The results of data processing indicate that the mental workload of operators at both stations is relatively high. The dominant factors contributing to the high workload are mental load and effort. The analysis also shows that the work system, environmental conditions, and physical demands are the main causes of the increase in NASA-TLX scores. These findings indicate the need for improvements in workload management and ergonomic aspects to improve operator welfare and productivity. It is recommended to implement interventions such as work shift arrangements, stress management training, and improvements to work facilities to reduce mental workload in the future.